Informing a Behavior Change Communication Strategy: Formative Research Findings From the Scaling Up Nutrition Movement in Mozambique. (September 2015) - Kodish, Stephen; Aburto, Nancy; Dibari, Filippo; Brieger, William; Agostinho, Saozinha P.; Gittelsohn, Joel
Background: Nutrition interventions targeting the first 1000 days show promise to improve nutritional status, but they require effective implementation. Formative research is thus invaluable for developing such interventions, but there have been few detailed studies that describe this phase of work within the Scaling Up Nutrition (SUN) movement. Objective: To inform a stunting prevention intervention in Cabo Delgado, Mozambique, by describing the sociocultural landscape and elucidating characteristics related to young child food, illness, and health. Methods: This formative research utilized a rapid assessment procedures (RAP) approach with 3 iterative phases that explored local perceptions and behaviors around food and illness among the Macua, Mwani, and Maconde ethnic groups. Ethnographic methods, including in-depth interviews, direct observations, free lists, and pile sorts, were used to collect data from community leaders, caregivers, and children 6 to 23 months. Data were analyzed drawing from grounded theory and cultural domain analysis. Results: Geographic differences drive sociocultural characteristics amid 3 ethnic groups that allow for segmentation of the population into 2 distinct audiences for behavior change communications. These 2 communities have similar classification systems for children's foods but different adult dietary patterns. Small-quantity lipid-based nutrient supplement did not fall into the existing food classification systems of either community, and participants preferred its promotion through community leader channels. Community members in both groups have little recognition of and perceived severity toward nutrition-related illnesses. Conclusion: Within Cabo Delgado, the cultural heterogeneity yields substantial differences related to food, illness, and health that are necessary to consider for developing an effective nutrition intervention.